Educational Quality Management in the First Cohort of The School Transformation Program in Batam - Nur Maladewi; Lantip Diat Prasojo (Dinasti Publisher, 2025)
This study aims to analyze the quality management of education in the first cohort of the Sekolah Penggerak program in Batam City, focusing on planning, implementation, evaluation, follow-up actions, as well as supporting factors, inhibiting factors, and resulting impacts. Key issues include teacher unpreparedness, limited competencies, technological barriers, and low parental involvement. The research employs the PDCA (Plan-Do-Check-Act) model using a qualitative multi-case study approach across 22 schools, with principals as primary subjects. Data were collected through interviews, observations, and document analysis, and analyzed inductively.The findings reveal that quality management was implemented in a structured manner: planning was participatory and data-driven using the SMART approach; implementation was adapted to school contexts through the Merdeka Curriculum, differentiated instruction, and technology integration; evaluation was conducted through assessments, reflections, and observations; and follow-up actions focused on enhancing teacher capacity, instructional methods, and school infrastructure. The success of the program was supported by school leadership, stakeholder collaboration, and government policies, although it faced challenges such as limited resources, resistance to change, and rigid bureaucracy.